Bifurcated bypass in severe chronic limb threatening ischaemia. (February 2022) - Adami, Daniele; Marconi, Michele; Piaggesi, Alberto; Mocellin, Davide M; Berchiolli, Raffaella N; Ferrari, Mauro
Objectives: Revascularization according to the angiosome concept is of proven importance for limb salvage in chronic limb threatening ischaemia but it is not always practicable. Bifurcated bypasses could be considered as an option when an endovascular approach is not feasible or has already failed and a single bypass would not allow direct revascularization of the ischaemic area. Bifurcated bypasses are characterized by landing on two different arteries, the main artery (in direct continuity with the foot vessels) and the secondary one (perfusing the angiosome district). The aim of this study is to evaluate the safety and effectiveness of bifurcated bypass in chronic limb threatening ischaemia. Methods: Thirty-five patients were consecutively treated with a bifurcated bypass for chronic limb threatening ischaemia from January 2014 to December 2019 in a single vascular surgery centre. Data from clinical records and operative registers were collected prospectively in an electronic database and retrospectively analysed. Primary and primary assisted bypass patency, amputation-free survival, morbidity and mortality rates at 12 and 24 months were analysed. Results: Mean follow-up period was 25.1 months (range 2–72 months). Thirty-six bifurcated bypasses were performed on 35 patients (age 75.3 ± 7.2 years; 69.4% were male). According to Wound, Ischemia, foot Infection classification 22.2% belonged to stage 3 and 77.8% to stage 4 and the mean Rutherford's class was 5.1 ± 0.7. Immediate technical success was 100%. Early mortality and morbidity rates were respectively 5.5%, and 33.3%; foot surgery was performed in 50% of cases with wound healing in all patients. Primary patency and primary assisted bypass patency were 96.7% and 100% at 6 months; 85.2% and 92% at 12 months, 59.9% and 73.4% at 24 months, respectively. Amputation-free survival at 12 and 24 months was, respectively, 95.6% and 78.8%. Overall survival rates at 12 and 24 months were respectively 94.4% and 91.6%. Conclusions: Bifurcates bypass can provide good results in patients with chronic limb threatening ischaemia without endovascular option, especially in diabetic ones. Bifurcated bypass is a complex surgical solution, both to be planned and performed, and it is quite invasive for frail patients that should be accurately selected.